The Policy Landscape: Enabling Cultural Heritage Businesses Through Government Initiative and Central Bank Intervention - STEELYANA, Evy (Journal of Tourism Economics and Policy, 2024)
This study examines the synergistic efforts of government regulations and Bank Indonesia (BI) initiatives in safeguarding Batik, as an intangible heritage, across diverse Indonesian provinces. Central and local government regulations underscore Batik's crucial role in preserving artistic traditions and national identity. Qualitative analysis is used by policies mapping technic and content analysis from the secondary data available in public domain. This study reveals a dedicated focus on cultural preservation by central government of which proven by multiple laws, a Presidential Decree, and Ministerial Regulations from various ministries. Regional policies align with central regulations, as evidenced by local government regulations in 26 provinces, showcasing tailored approaches and the local autonomy of provincial governments in upholding cultural perseverance. Bank Indonesia's comprehensive support aims for a vibrant and sustainable future by promoting Micro, Small, and Medium Enterprises (MSMEs) development through exhibitions, financial inclusion, and collaboration with local governments. Specific theme events relate to each region, such as Festival Meurah Silu in Aceh and Minang CrEFt in West Sumatra, highlight BI's dual focus on cultural preservation and economic empowerment. In conclusion, Indonesian government regulations in central and local government actively foster Batik preservation, ensuring the sustainability of cultural heritage and MSMEs development and Bank Indonesia's initiatives, intertwined with cultural preservation and economic empowerment.